PERANAN PENYULUH SEBAGAI DINAMISATOR DALAM BIMBINGAN TEKNOLOGI SL-PTT (SEKOLAH LAPANGAN PENGELOLAAN TANAMAN TERPADU) PADI INHIBRIDA DI DESA TEGAL YOSO KECAMATAN PURBOLINGGO KABUPATEN LAMPUNG TIMUR - Rahayu Ningsih; Irwan Effendi; Suarno Sadar (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This research aims to investigate: (1) the role of extension worker as a dynamisator in the technology guiding of SL-PTT (the field school of integrated plant management) for inhybrida rice plant; (2) the application of PTT (of integrated plant management) technology for inhybrida rice plant; (3) the correlation between the role of extension worker as a dynamisator and the application of PTT technology for inhybrida rice plant. This research was conducted on January to February 2013 in Tegal Yoso Village Purbolinggo District Lampung Timur Regency by using census method which is consist of 52 respondens. The research method was survey method.  The correlation between variables were tested by Rank Spearman Analysis. The results showed that (1) the role of extension worker as a dynamisator in the technology guiding of SL-PTT for inhybrida rice plant was in high cathegory, (2) the application of PTT technology for inhybrida rice plant was in midle cathegory; (3) there are a real correlation between the role of extension worker as a dynamisator and the application of PTT technology for inhybrida rice plant.   Key words: extension worker, inhibrida rice, role